Markers to Rapidly Distinguish Bacillus paralicheniformis From the Very Close Relative, Bacillus licheniformis - Olajide, Atinuke M.; Chen, Shu; LaPointe, Gisèle (Frontiers in Microbiology, 2021)
As close relatives, Bacillus paralicheniformis is often wrongly identified as Bacillus licheniformis. In this study, two genetic markers are presented based on fenC and fenD from the fengycin operon of Bacillus paralicheniformis to rapidly distinguish it from B. licheniformis. The fengycin operon is one of the few present in B. paralicheniformis but absent in B. lichenformis up to date. Using these markers, two presumptive B. paralicheniformis isolates each were recovered from a set of isolates previously identified as B. licheniformis by Matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) or identified only to genus level as Bacillus by 16S rRNA gene sequencing respectively. Whole genome sequencing of the four isolates confirmed their identity as B. paralicheniformis having the closest similarity with B. paralicheniformis ATCC 9945a (GenBank: CP005965.1) with a 7,682 k-mer score and 97.22 % ANI. Average Nucleotide Identity (ANI) of 100% suggests that the four isolates are highly similar. Further analysis will be necessary to determine if finer differences exist among these isolates at the level of single nucleotide polymorphisms.